Sterilization and Microbial Inactivation Technologies for Liquid Foods: A Review of Food Safety, Shelf Life, and Food-System Resilience in Indonesia - Loso Judijanto (Pt. Anagata Sembagi Education, 2026)
Liquid foods are highly susceptible to microbial contamination and quality deterioration, while distribution across geographically dispersed markets requires adequate shelf life, safety, and product stability. This article critically examines the development of sterilization and microbial inactivation technologies for liquid foods and evaluates their contribution to food safety and food-system resilience, with particular attention to Indonesia. Using a qualitative literature review, the study synthesizes peer-reviewed research published from 2020 to 2026 on thermal processes, particularly ultra-high-temperature (UHT)/aseptic processing and ohmic heating, and on non-thermal technologies including high-pressure processing (HPP), pulsed electric fields (PEF), ultraviolet-C (UV-C), and cold plasma. The synthesis shows that no single technology is optimal for every food matrix or safety target. UHT/aseptic processing remains the most established option when commercial sterility and ambient shelf stability are required, whereas HPP and PEF can provide superior retention of fresh-like quality but generally require additional hurdles when bacterial spores are relevant. UV-C performance is strongly constrained by optical properties, while cold plasma still requires broader product-specific validation, chemical-safety assessment, and scale-up evidence. For Indonesia, a portfolio approach is the most defensible strategy: optimize mature thermal and volumetric-heating platforms for mass-market products while developing targeted HPP, PEF, UV-C, and hybrid applications according to product properties, economics, regulatory requirements, and industrial capability